The electric motor and its work - Martin, Albert Edward (My University, 1891)
Introduction: There are two classes of persons whose influence is always detrimental to the inventor; the moss-back and the enthusiast. While mossbackism has in some degree retarded electrical progress, I believe that the crank with his wild hallucinations and farciful theories has even more prevented its legitimate development. When, with the year 1834, the Vermont blacksmith, Thomas Davenport, brought out his electric motor and a year later when the electric boat of Jacobi stemmed the waters of the river; it was claimed that steam was to be displaced and the “silent intangible something we call electricity” was to relieve man of the major portion of his work. It was even announced by Joule that power thus produced from a battery would be cheaper than steam power. The craze subsided and the application of the motor to practical work was attempted. At once it was seen that the substitution of zinc, a fuel only one-sixth as efficient and fifty times as costly; for coal could never be economical. This discovery that the supposed world conqueror was fit on by for the laboratory caused the public to lose all interest in the matter
Citation: Martin, Albert Edward. The electric motor and its work. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Electricity; Power; Iindustrialism; Electric motor; Davenport; Theses; Manuscripts (documents)